Development of Tracking Signal for Non-homogeneous Poisson Process Model - Mohd Faudzi, Mohamad Faeesol (IRC, 2021)
In this new age of rapid industrialization, which is daunting with the rapid speed of technological development, it is important to precisely make accurate prediction in order to stay relevant in the competitive market.